Extra-personal Schemas: In and out of Tourette’s Syndrome - James Park (Undergraduate Research Journal for the Human Sciences, 2016)
Most visible in Tourette’s syndrome (TS) is the display of sudden, brief, nonrhythmic, stereotyped movements and vocalizations known as tics. These displays are highly variable, differing not only in type—motor or phonic—but also along several dimensions of severity. Tic type is perhaps a chief distinction as the presence of multiple motor tics and at least one phonic tic is required for TS diagnosis (APA, 2000). While differences in tic severity do not enter into diagnostic criteria, considerable effort has been made at its characterization as well. In particular, the Yale Global Tic Severity Scale (YGTSS)—a widely respected and employed index for assessing tic severity—highlights five dimensions of severity including complexity, number, intensity, frequency, and interference (Leckman et al., 1989).
Keywords: Tourette; syndrome